2010
DOI: 10.1590/s0037-86822010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico da hanseníase em um município brasileiro, no período de 2000 a 2006

Abstract: INTRODUÇÃO: A hanseníase é considerada um grande problema de saúde pública nos países em desenvolvimento. Estima-se que somente 1/3 dos doentes sejam notificados e que, dentre esses, muitos fazem tratamento irregular ou o abandonam, aumentando o impacto da doença. Assim o objetivo desse artigo foi descrever o perfil epidemiológico da população com diagnóstico de hanseníase, no município de Uberaba, Estado de Minas Gerais, Brasil, no período de 2000 a 2006. MÉTODOS: Trata-se de um estudo retrospectivo, que util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
34
2
57

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 16 publications
10
34
2
57
Order By: Relevance
“…Regarding the ethnicity of patients, in our study, Caucasians were the predominant race, which differs from previous findings in the literature 32,35,36 where Mulatos were the most prevalent affected population. It should be noted that many patients who are from different regions of the state and who are users of the HUJM in Cuiaba are predominantly Caucasians.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the ethnicity of patients, in our study, Caucasians were the predominant race, which differs from previous findings in the literature 32,35,36 where Mulatos were the most prevalent affected population. It should be noted that many patients who are from different regions of the state and who are users of the HUJM in Cuiaba are predominantly Caucasians.…”
Section: Discussioncontrasting
confidence: 99%
“…Of the entire patient cohort, the age groups 14-33 and 34-53 years each represented one-third of the total patient population. This suggests that leprosy affects large number of individuals in the economically productive population, which causes high economic impacts due to their having to abstaining from work, caused by the development of permanent and physically disabling lesions 31,32 . Importantly, as these patients are not able to work, they have the right to seek sickness benefits and even disability retirement 33 .…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Although not signifi cant (p = 0.051), the results of this study suggest a higher level of education may contribute to the prevention of disabilities, an association which can be verifi ed with an increase in the number of cases analysed. Those with more time in the educational system, in addition to possibly having easier access to the health care system, may pay more attention to changes to their body, which may lead them to seek help earlier.…”
Section: Discussionmentioning
confidence: 54%
“…21 Disabilities and limitations in activities grow worse and become more frequent with age, irrespective of leprosy. 12,13,18 Professionals need to be aware of this fact and plan health care for this population bearing in mind the probable future need for further care.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to that observed by Monteiro et al 12 , who also found a predominance of low educational attainment among their study population. Low educational attainment affects treatment adherence and can make it difficult to interpret instructions about disability prevention 13 .…”
Section: Discussionmentioning
confidence: 99%